2013
DOI: 10.1099/vir.0.047423-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between structure, protein composition, morphogenesis and cytopathology of Glossina pallidipes salivary gland hypertrophy virus

Abstract: The Glossina pallidipes salivary gland hypertrophy virus (GpSGHV) is a dsDNA virus with rodshaped, enveloped virions. Its 190 kb genome contains 160 putative protein-coding ORFs. Here, the structural components, protein composition and associated aspects of GpSGHV morphogenesis and cytopathology were investigated. Four morphologically distinct structures: the nucleocapsid, tegument, envelope and helical surface projections, were observed in purified GpSGHV virions by electron microscopy. Nucleocapsids were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 94 publications
0
28
0
Order By: Relevance
“…We used a combination of proteogenomic and transcriptomic mapping approaches (Nesvizhskii, 2014) to complement the annotation of ORFs in the GpSGHVEth genome. In addition to using peptides identified from flies infected by GpSGHV-Eth, we also included data obtained from previous proteomics of the GpSGHVUga (Kariithi et al, , 2011(Kariithi et al, , 2013b(Kariithi et al, , 2016. Moreover, we compared the GpSGHV-Eth genome to the GpSGHVUga genome, which was annotated in silico (Abd-Alla et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used a combination of proteogenomic and transcriptomic mapping approaches (Nesvizhskii, 2014) to complement the annotation of ORFs in the GpSGHVEth genome. In addition to using peptides identified from flies infected by GpSGHV-Eth, we also included data obtained from previous proteomics of the GpSGHVUga (Kariithi et al, , 2011(Kariithi et al, , 2013b(Kariithi et al, , 2016. Moreover, we compared the GpSGHV-Eth genome to the GpSGHVUga genome, which was annotated in silico (Abd-Alla et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 86 proteins, 10, 15, 20 and 12 were classified as envelope, nucleocapsid, tegument and virion proteins, respectively, based on the detection of their homologues in highly purified GpSGHV-Uga virions by LC-MS/MS (Kariithi et al, 2013b). The remaining 29 of the 86 proteins without specific localization were designated infected cell-specific viral proteins (ICSVPs).…”
Section: Annotation Of 174 Orfs Potentially Expressed In the Gpsghv-ementioning
confidence: 99%
See 2 more Smart Citations
“…Following these basic studies, several virus management approaches were suggested [14] and the effect of two of these strategies on the prevalence of SGH in colonies of G. pallidipes was recently published i.e. adding the antiviral drug valacyclovir to the blood diet of the flies [15,16] and the application of a clean feeding strategy (each fly received a clean fresh blood meal each time) [17,18]. Briefly, the clean feeding system can be initiated in a large-scale colony by selecting as many cages of teneral flies from the main colony as can be fed at one time on the available clean membranes and thereafter these flies and their progeny should always be fed first on the fresh, clean blood (that has not been supplied to other flies).…”
Section: Resultsmentioning
confidence: 99%